INVESTIGATION OF MINERAL DEPOSIT SUSING AEROMAGNETIC DATA IN PART OF NORTH CENTRAL NIGERIA - Ugwu, Augustine Nnabuike; Ayanninnuola, Samuel Olatunji; Okenu, Chigozie Stella (FUDMA Journal of Sciences, 2026)
Karu and its surroundings are located in North Central Nigeria, within the middle belt of the Benue trough. This study analyzes high-resolution aeromagnetic data to provide insights into magnetic sources, structures, and potential mineralization zones in the area. The Total Magnetic Intensity data was examined using both qualitative and quantitative techniques, including reduced to equator, residual regional separation, First Vertical Derivative, Horizontal Derivative, Analytical Signal, and Source Parameter Imaging (SPI).Findings from the First Vertical Derivative and Analytical Signal maps indicate various structures with pronounced NE-SW trends, attributed to mega faults near Udeni, NE Brumburum, and NW Gofa. These areas display high structural intensity within sedimentary formations (sandstone, shale) and deep SPI depths, suggesting potential for base metals like lead and zinc, along with iron oxides.Depth estimations through SPI reveal that deep magnetic sources range from -46.352 to 90.252 nT, while shallow sources vary from -59.883 to 89.580 nT. The band pass analysis and integrated data from source parameter imaging and structural density delineate litho-structural controls on mineralization.High-priority zones identified include Uke, Gudi, Magayaikai, Keffi, Akwanga, Nasarawa, Garaku, and Bagaji, with Uke showing significant structural intensity, shallow SPI depths (~85.432 m), and notable geophysical anomalies.
Keywords: Basement; Structures; Spectral; Airborne Magnetics; Lineaments